Tingkah Laku Produksi Petani-Petani Gambir - Irnad, Irnad (Jurnal Embrio, 2009)
The aim of this research was to know the production behaviour of Gambier farmers behaviour in the watershed of Koto Panjang Dam. Production choices and efficiency behaviour are predicted by standar neoclassical theory. The production function is estimated from the farm survey conducted from Mei to June in 2009. The research result showed that R-C ratio of gambier farm was 1,75 and created frofit around six million rupiah per season per farm. The farm profit was influenced just by labour cost while there are no effect of fertilizer and herbicide cost, and social economy factors on farm profit. The use of fertilizer and herbicide are not allocatively efficient but the labour is almost allocatively efficient.